Service replication taxonomy in distributed environments. Issue 3 (September 2016) - Mohamed, Marwa
Abstract Abstract Nowadays, most modern distributed environments, including service-oriented architecture (SOA), cloud computing, and mobile computing, support replication technologies in order to improve operational characteristics of the services provided. Unfortunately, replication requires additional computational resources and a longer design and deployment process to implement service adequately for a specific situation and to enable service providers to maintain high levels of service with a moderate number of replicas. This paper provides a comprehensive review of replication challenges, types, techniques, and algorithms in distributed environments such as SOA, cloud, and mobile. Moreover, the role of replication in enhancing several QoS attributes, including performance, availability, security, scalability, and reliability, is examined. The author believes that the proposed research will help researchers to easily apply and develop the service replication in distributed system.